Similarities and differences between languages from a linguistic perspective - Hasanova , Sevinch Hotam qizi (The Lingua Spectrum, 2026)
This article focuses on comparing and contrasting languages, using the points of view of a linguistic criterion and seeks to offer a multi-level and systematic comparison of the linguistic structures. The discussion is done at major scales of linguistic description, which would be phonology, morphology, syntax, semantics, and pragmatics, to demonstrate how languages come together based on universal principles and how they go apart based on their language-specific patterns. Some of the fundamental linguistic universals identified by the study are the existence of lexical categories including nouns and verbs, simple clause structure, universal meaning and grammatical relationship expression mechanisms. Meanwhile, it focuses on idiosyncratic peculiarities which differ among languages, such as sound inventories, morphological typologies, word patterns, and pragmatic norms that are informed by cultural and social circumstances. Moreover, the article also talks about typological categories of languages taking into consideration how languages may be categorized based on structural characteristics such as the coping of analytics or synthetic morphology or the vocabulary order as fixed or flexible.